Evaluation of Modified Techniques for Toggle Pin Repair of Coxofemoral Luxation in Dogs: A Cadaveric Study - Helmick, Jacob I.; Bugbee, Suzanne E.; Strasberg, Jason R.; Franklin, Samuel P. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives The primary objective was to assess acetabular articular cartilage damage when an acetabular tunnel is drilled by passing the drill bit through the femoral tunnel. The second objective was to assess the success rate of passing the toggle through the femoral and acetabular tunnels in a single manoeuvre using a toggle delivery device.Methods Open bilateral coxofemoral luxations in 16 canine cadavers were repaired by toggle pin technique by a surgical resident (n = 8) and a diplomate surgeon (n = 8). In one hip of each cadaver, the acetabular tunnel was drilled through the femoral tunnel and the toggle was passed in a single manoeuvre using the delivery device. In the contralateral hip, the tunnels were drilled separately, and the toggle was passed through each tunnel separately (resident) or in a single manoeuvre (surgeon). Pelves were examined for acetabular cartilage damage and toggle placement.Results Cartilage damage did not occur with independent drilling of the acetabulum but occurred in 6/16 hips in which the acetabulum was drilled via the femoral tunnel. Successful deployment of the toggle was obtained in 24/24 hips in which the toggle was passed through the femoral and acetabular tunnels simultaneously using the delivery device, regardless of how the acetabular tunnel was drilled.Clinical Significance Drilling the acetabular tunnel through the femoral tunnel risks damaging the acetabular cartilage. Success was consistently obtained when passing the toggle through the femoral and acetabular tunnels simultaneously using the toggle delivery device.
Keywords: coxofemoral luxation; hip luxation; toggle pin; Arthrex Tightrope; dogs